2015
DOI: 10.1002/gepi.21950
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Set-Based Methods for Association Testing

Abstract: With a typical sample size of a few thousand subjects, a single genomewide association study (GWAS) using traditional one-SNP-at-a-time methods can only detect genetic variants conferring a sizable effect on disease risk. Set-based methods, which analyze sets of SNPs jointly, can detect variants with smaller effects acting within a gene, a pathway, or other biologically relevant sets. While self-contained set-based methods (those that test sets of variants without regard to variants not in the set) are general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…FLAGS showed consistent high performance over a wide range of disease models. The robustness of FLAGS is consistent with a recent study that found the adaptive rank truncated product (ARTP) to perform best in a comparison of a number of set-based association tests (Su et al 2015). The ARTP adaptively seeks a subset of SNPs that yields the best evidence for genetic association.…”
Section: Discussionsupporting
confidence: 79%
“…FLAGS showed consistent high performance over a wide range of disease models. The robustness of FLAGS is consistent with a recent study that found the adaptive rank truncated product (ARTP) to perform best in a comparison of a number of set-based association tests (Su et al 2015). The ARTP adaptively seeks a subset of SNPs that yields the best evidence for genetic association.…”
Section: Discussionsupporting
confidence: 79%
“…Finally we compare the power of three omnibus tests: oTFisher with soft-thresholding, the adaptive TPM (ATPM, hard-thresholding), and the adaptive RTP (ARTP). ARTP was shown to have the highest power among a group of adaptive set-based methods for genetic association testing (Su et al, 2016;Yu et al, 2009). The Supplementary Figures S1 and S2 in the Supplementary Materials illustrate the power of the optimal TFisher and the three omnibus tests under the same settings as Figures 11 and 12, respectively.…”
Section: Statistical Power Comparison For Signal Detectionmentioning
confidence: 99%
“…The p-value combination methods have been widely used for genetic association studies, but most of them were based on hard-thresholding, including TPM and RTP methods (Biernacka et al, 2012;Dai et al, 2014;Dudbridge and Koeleman, 2003;Hoh et al, 2001;Li and Tseng, 2011;Su et al, 2016;Yu et al, 2009). In this section we apply and assess the soft-thresholding TFisher by analyzing a whole exome sequencing data of amyotrophic lateral sclerosis (ALS).…”
Section: Als Exome-seq Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no uniformly most powerful test, it is desirable to apply an adaptive test such that high power can be maintained against various alternatives (e.g. Chen et al 2010;Lee et al 2012;Zhang et al 2014;Su et al 2015;Huang et al 2016;Su et al 2017;Ma and Wei 2019;Yang et al 2019), most of which require Monte Carlo methods to calculate their p-values. Pan et al (2014) proposed such a test, called the adaptive sum of powered score (aSPU) test, based on combining a family of so-called sum of powered score (SPU) tests, which cover some existing tests, such as the Sum (or burden) test, the sum of squared score test (Pan 2009)…”
Section: Introductionmentioning
confidence: 99%